High-temperature metamorphism in the western Namaqua-Natal Metamorphic Province (South Africa): implications for low-pressure granulite terranes - Schorn, Simon (Department of Geological Sciences, 2019)
The interpretation of pressure (P)-temperature (T)-time (t) data is key to reconstruct the geologic evolution of ancient exhumed orogens. Of these, temperature is regarded as proxy for the heat energy available during orogenic metamorphism. Heat - the ultimate driving force of metamorphism - is consumed by a number of processes occurring during orogeny. Metamorphic rocks evolve through chemical reactions that consume energy in order to advance. As long as strongly energy-intensive processes advance in the crust, the temperature that is effectively attained is controlled by the interplay between the rate of heat energy supplied to the site of reaction and the rate of heat consumed by the process(es). Melting reactions in particular are strongly endothermic and consume a substantial proportion of the orogenic heat budget. Fertile metapelites are volumetrically minor but petrologically significant, as P-T-t-deformation constraints and burial-exhumation paths are preferentially derived from this lithology, whereas refractory granites sensu lato compose the bulk of orogenic crust. Metapelites are affected by a number of heat-consuming reactions that cause a near-isothermal state as long as they advance, however granites intersect few endothermic meltproducing reactions during orogenic metamorphism. Granitoids therefore may effectively reach a higher temperature compared to metapelites exposed to the same heat input. Temperature determined from metapelites may therefore not represent the true thermal maximum experienced by a portion of metamorphic crust - especially in granulite terranes where partial melting is widespread. Because temperature is an effect rather than the cause of heat energy transferred into the crust, it may not represent the most geodynamically relevant parameter to describe metamorphism. In this study a suite of supracrustal litholgies from the Bushmanland Subprovince (BSP) of the Namaqua-Natal Metamorphic Province (NNMP) of southern Africa are investigated via thermodynamic modelling and zircon-monazite U-Pb in-situ geochonology. Regional P-T-t distribution reveals a complex polyphasic evolution with two major tectonometamorphic episodes at ∼1.2-1.1 and 1.04-1.0 Ga, respectively. The older event is temporally linked to the emplacement of the felsic pre- to syn-tectonic Little Namaqualand Suite that caused widespread greenschist- to amphibolite facies contact metamorphism. This is recorded in garnet-cordierite-sillimanite gneisses exposed at the northernmost locality investigated here and as cm-sized porphyroblasts (e.g. andalusite) hosted in rare Mg-Al-rich gneisses. The younger event is characterised by granulite facies metamorphism peaking at 1040-1000 Ma in the entire BSP, with pelitic granulites recording variable apparent temperatures of between ∼760 and <900 ◦C at 5-6 kbar. Coarse-grained porphyroblasts of andalusite in an example of Mg-Al-rich gneiss were replaced by symplectites of high-grade phases during heating at the granulite event. At upper-greenschist facies conditions the immobility of Al caused the formation of monomineralic coronae at the expense of andalusite, effectively isolating the porphyroblasts from the matrix. Diffusion of Fe + Mg along respective gradients of µFe and µMg with simultaneous immobility of Al + Si led to the breakdown of andalusite to symplectites of cordierite + spinel during near-isobaric heating to peak conditions. Monomineralic coronae of sapphirine developed during near-isobaric cooling at the expense of previously-formed symplectites. Detailed investigation of a conformable sequence of sedimentary and mafic granulites from the locality Hytkoras in central Bushmanland reveal a disparity of some 60-70 ◦C in estimated peak metamorphic temperature. Aluminous metapelites equilibrated at ∼770-790 ◦C whereas two-pyroxene granulite and garnet-orthopyroxene-biotite gneiss record distinctly higher conditions of ∼830-850 ◦C. Semipelite and Mg-Al-rich gneisses yield poorly-constrained estimates that span the range derived from other lithologies. All samples record peak pressure of ∼5-6 kbar, and followed a roughly isobaric heating path from andalusite-greenschist / lower-amphibolite facies conditions through a tight clockwise loop at near-peak conditions, followed by near-isobaric cooling. The disparity in peak temperatures appears to be robust, as the low-variance assemblages in all samples reflect well-known melting reactions that only occur over narrow temperature intervals. The stable coexistence of both products and reactants of these melting reactions indicates that they did not go to completion before metamorphism waned. vi Calculated pressure-enthalpy diagrams show that the melting reactions are strongly endothermic and therefore buffer temperature while heat is consumed by melting. Because the respective reactions occur at distinct P-T conditions and have different reactant assemblages, individual lithologies are thermally buffered at different temperatures and to different degrees, depending on the occurrence and abundance of reactant minerals. If little to no thermal communication is assumed, this implies that lithology exerts a first-order control over the heating path and the peak temperature that can be attained for a specific heat budget. Calculations show that all lithologies received essentially the same suprasolidus heat budget of 19 ± 1 kJ.mol−1 , which led to manifestation of lower peak temperatures in the more fertile and strongly buffered aluminous metapelites compared to more refractory rock types. The heat source responsible for near-isochronous high-grade metamorphism at a regional scale most likely was a mixture of mafic mantle underplating combined with radiogenic heating in a slowly buried juvenile crust. Heat transfer to higher levels of the crust was aided by advective heating via the syn-metamorphic emplacement of the post-tectonic Spektakel Suite that locally led to near-ultrahigh temperature (UHT) conditions recorded by proximal pelitic granulites. The overall characteristics of the BSP, namely (i) heating from shallow low-grade conditions to granulite facies temperatures at a maximum depth of ∼20 km along a roughly isobaric heating path with minor concomitant burial, (ii) seemingly coeval peak metamorphism recorded at a regional scale that was accompanied/preceded by voluminous felsic magmatism (iii) that was followed by (iv) slow, largely isobaric cooling to an ambient geotherm with no significant attending exhumation, are consistent with a long-lived evolution in a continental back-arc mobile belt setting.